Museum activism - Janes, Robert R., 1948-; Sandell, Richard, 1967- (Abingdon, Oxon ; New York, NY : Routledge, 2019)
"Only a decade ago, the notion that museums, galleries and heritage organisations might engage in activist practice, with explicit intent to act upon inequalities, injustices and environmental crises, was met with scepticism and often derision. Seeking to purposefully bring about social change was viewed by many within and beyond the museum community as inappropriately political and antithetical to fundamental professional values. Today, although the idea remains controversial, the way we think about the roles and responsibilities of museums as knowledge-based, social institutions is changing. Museums and Activism examines the increasing significance of this activist trend in thinking and practice. At this crucial time in the evolution of museum thinking and practice, this ground-breaking volume brings together more than fifty contributors working across six continents to explore, analyse and critically reflect upon the museum's relationship to activism. Including contributions from practitioners, artists, activists and researchers, this wide-ranging examination of new and divergent expressions of the inherent power of museums as forces for good, and as activists in civil society, aims to encourage further experimentation and enrich the debate in this nascent and uncertain field of museum practice. Museum Activism elucidates the largely untapped potential for museums as key intellectual and civic resources to address inequalities, injustice and environmental challenges. This makes the book essential reading for scholars and students of museum and heritage studies, gallery studies, arts and heritage management and politics. It will be a source of inspiration to museum practitioners and museum leaders around the globe"--
Whose memories for which future? Favela museums and the struggle for social justice in Brazil / Marcelo Lages Murta -- From vision to action: the journey towards activism at St. Fagans National Museum of History / Sioned Hughes and Elen Phillips -- Active museums: inside out / Moya McFadzean, Liza Dale-Hallett, Tatiana Mauri and Kimberley Moulton -- Quiet is the new loud? : on activism, museums and changing the world / Åshild Andrea Brekke -- Heritage and queer activism / Sean Curran -- The activist spectrum in United States museums / Dina A. Bailey -- Up against it: contending with power asymmetries in museum work / Kevin Coffee -- Taking a position: challenging the anti-authorial turn in art curating / Lynn Wray -- Memory activism and the holocaust memorial institutions of the 21st century / Diana I. Popescu -- Advocacy and activism: a framework for sustainability science in museums / Sandra L. Rodegher and Stacey Vicario Freeman --^
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Museum exhibits; Museums -- Educational aspects; Museums -- Political aspects; Museums -- Social aspects; Social influence; Social justice